Identifying opinion leaders in the #StopHateForProfit campaign through Social Network Analysis - Puerta-Díaz, Mirelys [UNESP]; Martínez-Ávila, Daniel; Ovalle-Perandones, María-Antonia (Editorial CSIC, 2025)
This study addresses the #StopHateForProfit boycott campaign against Facebook from a Social Network Analysis (SNA) perspective, using natural language processing to examine data collected from the Twitter social network site (now X). SNA revealed the international nature of the participating community, and with indicators of degree centrality, betweenness, and closeness metrics, its social structure and most influential actors were examined. The campaign mobilized a diverse range of participants and the formation of a cohesive community was identified. Over 1,000 companies stood out, including major brands like Adidas and Coca-Cola, civil rights advocacy organizations, public figures, entertainment industry representatives, as well as members of civil society. Predominant themes in the overall narrative were identified, sparking discussions on broader issues such as corporate social responsibility, civil rights, social inequalities, and the phenomenon of misinformation.
Identificando líderes de opinión en la campaña #StopHateForProfit a partir del Análisis de Redes Sociales
Keywords: #StopHateForProfit; análisis de redes sociales; discurso de odio; Facebook; hate speech; social network analysis